THE SYSTEM OF IMPOSING FINES AND ITS EFFECTIVENESS IN REDUCING FRAUD IN PERUM PEGADAIAN PRODUCTS IN THE CONTEXT OF TA’WIDH - Mujahid Muthahhari; Jamhuri; Nahara Eriyanti (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
The penalty system and its effectiveness in reducing fraud in Perum Pegadaian products are examined through the lens of ta’widh. Ta’widh is a form of compensation imposed on customers due to negligence or delay in fulfilling contractual obligations, intended to cover the actual losses suffered by Islamic financial institutions, not as a means of profit-seeking. This study focuses on the mechanism for imposing fines at Perum Pegadaian, their effectiveness in preventing fraud and customer default, and their conformity with the principle of ta’widh as defined in sharia provisions. This study uses a normative empirical method with a descriptive qualitative approach. Data were obtained through interviews with Pegadaian Syari’ah employees and analysis of relevant documents. The results show that the penalty system at Perum Pegadaian serves a preventive function, improving payment discipline and reducing the potential for fraud through deliberate late payments and contract misuse. However, in practice, penalties are still imposed on a standard basis and are included in the contract, so they may not fully reflect the actual losses as required by the principle of ta’widh. This study suggests that the penalty system at Perum Pegadaian is functionally effective in reducing fraud but needs improvement to better align with the principles of justice and Sharia compliance, particularly in determining the amount of ta’widh based on actual losses.